Policies to Mitigate the Socio-economic Impact of the Global Financial Crisis on Sudan - Elbeely, Khalid Hassan (Advances in Social Sciences Research Journal, 2015)
This study aimed at examining the socio-economic impact of the global financial crisis (GFC) on Sudan; specifically its impact on: Balance of Payment performance (with emphasis on exploring its effect on both Foreign Direct Investment (FDI) and Remittances of Sudanese expatriates); inflation rates; Gross Domestic Product (GDP) growth rate; exchange rate; unemployment; and poverty. Moreover, the proposed policies to mitigate the negative impact which may take place as a result will be assessed critically. This study indicated that the GFC had an adverse effect on both the economic and social indicators, which had been examined. Accordingly, it lowered exports, caused FDI and remittances to drop, thus widening the balance of payments deficit. Furthermore, inflation and unemployment rates both rose to 12.1% and 18.7% in the years followed the crisis, with inflation recording 45.8% in 2012. In addition, GDP growth rates declined to 5.9% and 5.2% in the years 2009-2010 that followed the crisis, and even to 1.9% and 1.1% in 2011-2012 respectively. Moreover, the Sudanese pound lost 21.5% of its value immediately after the crisis, as well as almost 100% of its value during the period 2011-2012, while poverty rates loom high at 46.5%. A set of policies were proposed in order to contain the negative impact of GFC.